2015
DOI: 10.1016/j.ultramic.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

High-speed dynamic atomic force microscopy by using a Q-controlled cantilever eigenmode as an actuator

Abstract: Keywords:Atomic force microscope High-speed dynamic AFM Fast actuation Q-controlled eigenmode of a cantilever a b s t r a c tWe present a high-speed operating method with feedback to be used in dynamic atomic force microscope (AFM) systems. In this method we do not use an actuator that has to be employed to move the tip or the sample as in conventional AFM setups. Instead, we utilize a Q-controlled eigenmode of an AFM cantilever to perform the function of the actuator. Simulations show that even with an ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…We found that the minimum required time to image that feature with a specific accuracy is 360 μs. 19 We also found that the imaging bandwidth is almost directly proportional to the cantilever resonance frequency. Given that information we expect that the maximum modulation frequency must be about (1/360 μs) × (113 kHz/ 300 kHz) ≈ 1 kHz.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…We found that the minimum required time to image that feature with a specific accuracy is 360 μs. 19 We also found that the imaging bandwidth is almost directly proportional to the cantilever resonance frequency. Given that information we expect that the maximum modulation frequency must be about (1/360 μs) × (113 kHz/ 300 kHz) ≈ 1 kHz.…”
Section: Resultsmentioning
confidence: 53%
“…It was shown theoretically under certain conditions that 24 frames/s imaging speed can be achieved with a cantilever having a resonance frequency of 600 kHz to acquire 100 × 100 pixels image in the FM-AFM system. 19 Hence we expect a faster imaging speeds by using small cantilevers with spring constants less than 1 N/m and resonance frequencies greater than 1 MHz as employed in systems with optical beam deflection detection. 5,6 As the high-speed AFM applications growing rapidly, the presented technique could help to advance the current technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the data transfer and processing capabilities will limit the data acquisition speed [ 7 ]. Various approaches have been used to resolve this problem, such as: (i) designing a new type of actuator [ 8 ]; (ii) improving both the optical beam deflection and the electronic readout systems [ 3 ]; (iii) using a self-actuating high quality piezoelectric lead zirconate titanate (PZT) cantilever with piezo resistors [ 9 ]; (iv) using small cantilevers [ 10 ]; (v) using a high-resonant-frequency cantilever [ 11 ]; (vi) using high resonance frequency, thermally actuated piezo-resistive cantilevers [ 12 ]; (vii) utilizing a Q-controlled natural vibration shape of an AFM cantilever to perform the function of the actuator [ 13 ]; (viii) a control system approach [ 14 ]. All these ideas are based on the introduction of new devices to the sensory part or for improvement of the AFM control system.…”
Section: Introductionmentioning
confidence: 99%